2003
DOI: 10.4067/s0717-65382003000100013
|View full text |Cite
|
Sign up to set email alerts
|

Phyllocaulis Gayi (Pulmonata: Systellommatophora): A Neglected Granivore in Chilean Temperate Forests?

Abstract: Evidence is advanced suggesting that Phyllocaulis gayi, a large slug in the temperate forests of Chile, might be a significant but overlooked granivore. In a short-term experiment, up to 18% of seeds are preyed upon by P. gayi. The intensity of seed predation is significantly reduced in forest fragments.KEYWORDS: Forest fragmentation, granivory, invertebrates, Nothofagus, Phyllocaulis. RESUMENPresentamos evidencia que Phyllocaulis gayi, una babosa de gran tamaño, podría ser un granívoro ignorado en los bosques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2007
2007
2010
2010

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Simonetti et al (2003) reported that the large slug Phyllocaulis gayi was responsible for 14.2% of the predation of Arachis hypogea seeds offered in Chilean temperate forests. The slug was also observed to feed on seeds of native trees in the laboratory.…”
Section: Seed Consumption By Different Animal Taxamentioning
confidence: 99%
See 1 more Smart Citation
“…Simonetti et al (2003) reported that the large slug Phyllocaulis gayi was responsible for 14.2% of the predation of Arachis hypogea seeds offered in Chilean temperate forests. The slug was also observed to feed on seeds of native trees in the laboratory.…”
Section: Seed Consumption By Different Animal Taxamentioning
confidence: 99%
“…The most prominent seed predators in forests are rodents (Janzen 1971;Heithaus 1981) and arthropods, in particular, carabid beetles, although many insects have been shown to prey on plant seeds (Cardina et al 1996;Ohkawara et al 1996;Honek et al 2003;Hurst and Doberski 2003;O'Rourke et al 2006;White et al 2007). One group of seed predators that has so far received little attention is the gastropods even though slugs and snails have been reported to prey on seeds (Cardina et al 1996;Kollmann and Bassin 2001;Hurst and Doberski 2003;Simonetti et al 2003). Elaiosomes on seeds of myrmecochorous plants have a dual role: on the one hand, they attract ants, the natural seed dispersers; on the other hand, elaiosomes may also attract a diverse invertebrate fauna, including insects (Ohkawara et al 1996), slugs, and snails (Mesler and Lu 1983;Muir 1997), which feed on the elaiosomes and may damage seeds.…”
Section: Introductionmentioning
confidence: 99%
“…Leidyula fl oridana was found at various places in the state of Nuevo León by Contreras-Arquieta (1995, 2003 (Table 1), but he did not comment on special features of the species. Particular importance should be given to Contreras-Arquieta's records of L. fl oridana in Tlapacoyan, Veracruz and Tapachula, Chiapas, since these places are far from Nuevo León.…”
Section: Remarksmentioning
confidence: 99%
“…Ecological notes. Phyllocaulis gayi lives in temperate forest in southern Chile (Thomé, 1976), and although general knowledge considers slugs as herbivores, Simonetti et al (2003) observed P. gayi feeding in the fi eld on seeds of the exotic Arachis hypogea; in addition, in laboratory experiments it consumed seeds of the native trees Cryptocarya alba and Aetoxicum punctatum (Simonetti et al, 2003); in the opinion of these authors, P. gayi should be considered a potential seed predator in forest regeneration and should be monitored carefully.…”
Section: Taxonomic Summarymentioning
confidence: 99%